Assessing The Drivers Of Educational Success: Administrative Capacity, Enabling Conditions, And The Localization Of SDG 4 (Quality Education) (Architecture Image Studies, 2026)
The translation of global education goals into local realities remains a critical challenge. This study assesses the relative predictive influence of Administrative Capacity (internal resources) and Enabling Conditions (external environment) on the localization of SDG 4 (Quality Education). Utilizing a quantitative cross-sectional design, data were collected from 500 Thai educational administrators. Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis revealed that both factors are significant positive predictors (p < .001), but Enabling Conditions (β = 0.495) had a substantially greater predictive impact than Administrative Capacity (β = 0.342). These findings indicate that successful localization is driven more by the external environment, specifically, political will and policy coherence, than by internal resources alone. This suggests that policymakers must prioritize institutional reforms to accelerate the effective achievement of quality education.